2003
DOI: 10.1051/vetres:2003011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation of metabolic-intermediate cytochrome P450 complexes in rabbit liver microsomes by tiamulin and various macrolides

Abstract: -Tiamulin and a number of macrolides were evaluated as to their ability in forming metabolic-intermediate (MI) complexes with cytochrome P450 in liver microsomes from rabbits bred for meat production. Complex formation, which occurred only in preparations where the expression of P450 3A was increased as the result of rifampicin pre-treatment and with different kinetics, was in the order tiamulin > erythromycin > TAO » roxithromycin » tylosin and did not take place with tilmicosin and spiramycin. Most of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These results came fit with the results of Fayez et al [40] who revealed that enramycin treatment had a negative effect on the liver that cause a distinctive elevation in the serum level of ALT and AST in broilers. The main threated effect of antibiotics on the liver is through its metabolism in the liver that mainly causes a great damage to the hepatic cells [41]. In the current study, the synbiotic treatment in this study, have no positive or negative effects on the liver and kidney healthiness.…”
Section: Resultsmentioning
confidence: 59%
“…These results came fit with the results of Fayez et al [40] who revealed that enramycin treatment had a negative effect on the liver that cause a distinctive elevation in the serum level of ALT and AST in broilers. The main threated effect of antibiotics on the liver is through its metabolism in the liver that mainly causes a great damage to the hepatic cells [41]. In the current study, the synbiotic treatment in this study, have no positive or negative effects on the liver and kidney healthiness.…”
Section: Resultsmentioning
confidence: 59%
“…At 125-μM concentration, the extent of CYP3A MI complexation was in the order of tiamulin>erythromycin> TAO>roxithromycin>tylosin, but non-detectable with spiramycin and tylmicosin [262] Finally, HIV-protease inhibitors such as amprenavir, indinavir, nelfinavir, lopinavir, saquinavir, and RTV have long been known as potent P450 inhibitors [263][264][265][266][267][268][269][270] When their MBI potential was tested using pooled HLMs, recombinant rCYP3A4 (+b 5 ), and rCYP3A5 (+b 5 ), with CYP3A -dependent testosterone 6β-hydroxylation as the functional probe [31,271], all these agents exhibited time-and concentrationdependent MBI, with RTV ( See Fig 515) being not only the most potent ( K I = 0.10 and 0.17 μM, respectively), but also the most efficient ( k inact = 0.32 and 0.42 min − 1 , respectively) against rCYP3A4 (+b 5 ) and HLMs [271] On other hand, nelfinavir was the most efficient inactivator of CYP3A5 ( k inact = 0.47 min − 1 ) and RTV, the most potent (K I = 0.12 μM). Most importantly, all of these HIV-protease inhibitors with the exception of lopinavir and saquinavir were also found to exhibit spectrally detectable MI complexation of rCYP3A4 (+b 5 ) [271] This is particularly intriguing for RTV, whose potential for MI complexation is not entirely obvious from either its chemical structure or its major site of oxidation (See Fig 515) While the role of RTV as a potent CYP3A inhibitor is incontrovertible and supported by ample in vivo data, the mode of this inhibition remains highly controversial To date, the mechanisms of its CYP3A inhibition include: Irreversible type II binding with consequent lowering of the P450-heme redox potential to effectively block CPR-electron transfer [272], MBI via MI complexation [271], and MBI via heme-adduction to the CYP3A protein [265, 273; see below] Although supportive experimental evidence exists for each of these mechanisms, it is puzzling how the virtual catalytic blockade invoked in the first mechanism could ever be reconciled with the other two inactivation modes that require P450 catalytic turnover and thus CPR-reduction…”
Section: Aq1mentioning
confidence: 96%
“…The tertiary amine macrolide antibiotic s erythromycin and troleandomycin (TAO; Fig 56) The broad-spectrum macrolide antibiotic clarithromycin (Fig 56) has been shown to form hepatic CYP3A -MI complexes when administered to control or dexamethasone (DEX)-pretreated rats [229,260] In vitro studies with DEX-pretreated rat liver microsomes (enriched in CYP3A content) revealed that MI complexation was most efficient with clarithromycin N-oxide and N-desmethylclarithromycin relative to the parent compound both in their time of onset as well as extent Repeated intraperitoneal administration of these compounds to rats also revealed that these two metabolites were more efficient than the parent compound in "inducing" hepatic P450 content, albeit not quite as potently as TAO [260] Biopsy sampling of the duodenal mucosa of human volunteers repeatedly administered clarithromycin (500 mg twice daily/7 d) revealed that it also reduced their duodenal CYP3A-dependent 1ʹ-hydroxymidazolam and 4-hydroxymidazolam hydroxylation by 74and 63 %, respectively, versus the corresponding baseline values [261] This clarithromycin-elicited lowering of the intestinal CYP3A content was associated with a doubling of the dose-normalized midazolam plasma concentration after intravenous administration and a corresponding decrease in the ratio of serum 1ʹ-hydroxymidazolam/midazolam relative to baseline values, consistent with the observed doubling of the gut wall bioavailability of oral midazolam [247] Immunoblotting analyses revealed a small, albeit not statistically significant increase in intestinal CYP3A4/5 content normalized to villin content, consistent with possible CYP3A stabilization upon clarithromycin-elicited MI complexation [261] Furthermore, individuals exhibiting overall higher CYP3A activity due to expression of both CYP3A4 and functionally active CYP3A5 were proposed to be at a greater risk for clarithromycin-elicited DDIs than individuals lacking functional CYP3A5 expression [261] The macrolide antibiotic tiamulin, a semisynthetic derivative of the antibiotic pleuromutilin, is used in meat producing domestic animals in Europe and Mediterranean countries for the treatment of enteric and respiratory diseases, and such use in veterinary medicine is associated with toxic DDIs, when coadministered with other P450 competitive drug substrates or inhibitors Indeed, tiamulin was also found to generate MI complexes with CYP3A enriched rifampin-pretreated rabbit liver microsomes [262]. At 125-μM concentration, the extent of CYP3A MI complexation was in the order of tiamulin>erythromycin> TAO>roxithromycin>tylosin, but non-detectable with spiramycin and tylmicosin [262] Finally, HIV-protease inhibitors such as amprenavir, indinavir, nelfinavir, lopinavir, saquinavir, and RTV have long been known as potent P450 inhibitors [263][264][265][266][267]…”
Section: Aq1mentioning
confidence: 99%